The use of biofuels and bioliquids in the European Union in the context of sustainable development and food security's constraints - Catalin Voica; Corina Ene; Mirela Panait (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The sectors of transport and energy are at a turning point, which is generated by various factors such as climate change, population growth and its reliance on classic fuels , the necessity of access to modern energy services for the rural population. The solution would be widespread use of renewable sources in final consumption and in transport. Based on these considerations , the authors aim to present their analysis of the situation of the EU market for biofuels and bioliquids. On the one hand, the use of biomass ensures a sustainable approach to energy consumption, but, on the other hand, it raises the issue of food security.
Keywords: Q1; Q2; 330; biofuels; sustainable development; food security; renewable energy